Research on tire tread abrasion performance considering the patten and slippage with verification - Huaqiao Liu; Yao Xiao; Kongshuo Wang; Yukun Zhou; Huiguang Bian; Chuansheng Wang (Polymer Testing)
The wear, rolling resistance, and wet grip are the most important performance of tires. The wear of tires rubber is influenced by various factors such as formula composition (such as butadiene rubber content), rubber strength, heat generation performance, etc. It is a complex problem involving mechanics and thermodynamics. Unfortunately, commonly used wear testing equipment in the tire industry, such as DIN abrasion, Akron abrasion, and Lambourn abrasion, cannot accurately characterize the wear performance of tires. The ABS control slippage during vehicle acceleration and braking provides sufficient grip in contact with the road surface, which is the most critical cause of tire wear. The wear performance of rubber at different slippage is a key factor affecting tire life. In this study, three compounds were developed, differing significantly in hardness, modulus, and the filling ratio of silica, to be manufactured as tire tread. The slippage was calculated with the results of the tire pattern model and pressure blanket tests. Subsequent wear performance tests were conducted on a fully automated wear testing machine under different slippage. Compared to the DIN and Cut-chip test results, the correlation with the taxi road test outcomes was enhanced when different slip rates were considered. This study introduces a novel method for assessing wear by calculating the tire slippage. By accounting for variables such as tire pattern and rubber rigidity, the slippage under ABS-controlled conditions was determined. Consequently, the wear performance demonstrated a stronger correlation with tire mileage as evidenced by the taxi road tests.